A dual role for proline iminopeptidase in the regulation of bacterial motility and host immunity. (16th April 2018) - Kan, Jinhong; An, Lin; Wu, Yao; Long, Jia; Song, Liyang; Fang, Rongxiang; Jia, Yantao
Summary: During plant–pathogen interactions, pathogenic bacteria have evolved multiple strategies to cope with the sophisticated defence systems of host plants. Proline iminopeptidase (PIP) is essential to Xanthomonas campestris pv. campestris ( Xcc ) virulence, and is conserved in many plant‐associated bacteria, but its pathogenic mechanism remains unclear. In this study, we found that disruption of pip in Xcc enhanced its flagella‐mediated bacterial motility by decreasing intracellular bis‐(3′, 5′)‐cyclic dimeric guanosine monophosphate (c‐di‐GMP) levels, whereas overexpression of pip in Xcc restricted its bacterial motility by elevating c‐di‐GMP levels. We also found that PIP is a type III secretion system‐dependent effector capable of eliciting a hypersensitive response in non‐host, but not host plants. When we transformed pip into the host plant Arabidopsis, higher bacterial titres were observed in pip ‐overexpressing plants relative to wild‐type plants after Xcc inoculation. The repressive function of PIP on plant immunity was dependent on PIP's enzymatic activity and acted through interference with the salicylic acid (SA) biosynthetic and regulatory genes. Thus, PIP simultaneously regulates two distinct regulatory networks during plant–microbe interactions, i.e. it affects intracellular c‐di‐GMP levels to coordinate bacterial behaviour, such as motility, and functions as a type III effector translocated into plant cells to suppress plant immunity. Both processes provide bacteria with the regulatory potential to rapidly adapt to complex environments, to utilize limited resources for growth and survival in a cost‐efficient manner and to improve the chances of bacterial survival by helping pathogens to inhabit the internal tissues of host plants.